Bioactivities and analysis of peptides from Sumbawa horse milk generated by Bacillus thuringiensis protease - Eni Kusumaningtyas; R. Widiastuti; H. D. Kusumaningrum; M. T. Suhartono (Indonesian Center for Animal Research and Development (ICARD), 2016)
Sumbawa horse milk is claimed to cure some diseases such as asthma, hypertension, diabetes and gastrointestinal disorder but its potential bioactive peptide has not been explored. The aims of this study are to evaluate bioactivities peptides from Sumbawa horse milk protein hydrolysate and to analyzethe physio-chemical properties of selected peptides. The milk protein was hydrolyzed by Bacillus thuringiensis protease, the peptide produced were sequential fractionated and then analyzed for antibacterial and antioxidant activities. The peptide fraction <3 kDa was then sequenced using LCMS-MS and the physio-chemical properties of the peptides were analyzed. The result showed that peptides fraction <3 kDa from the 30 min hydrolysis was the most active as antibacterial and more active to Gram negative bacteria. For antioxidant, scavenging activity of the fraction per µg protein/mL were 83% to ABTS and 31% to DPPH radicals. The values were similar with vitamin C 12.5 µg/mL for ABTS and 14.5 µg/mL for DPPH. Peptide HPYFYAPELLYYANK with molecular weight prediction 1887.92 Da and isoelectric point 7.47 has high therapeutic index prediction (64.75). The result showed that peptides from Sumbawa horse milk hydrolyzed by Bacillus thuringiensis protease was active as antibacterial and antioxidant. Peptide HPYFYAPELLYYANK from fraction <3 kDa was potential as antibacterial.